METHODOLOGICAL FEATURES OF THE DEVELOPMENT OF THE FORM OF GOVERNANCE IN THE CONTEXT OF CONSTITUTIONAL STABILITY - Manasyan, Anahit (State and Law, 2022)
Article considers issues with regard to methodological features of the development of the form of governance in the context of constitutional stability. Author concludes that while speaking on the forms of governance we are often guided by fictional perceptions, which should be overcome and cannot base reforms concerning the mentioned issue. In the result of processes of legal convergence forms of governance borrowed from each other mechanisms non-characteristic to them and from this aspect in many cases their rapprochement can be noted. From the doctrinal viewpoint author considers classical forms of governance more acceptable. At the same time, she notes that the problems of our social system, solution of which is the main reason for continuous changes of the form of governance, will not be solved in conditions of new reforms implemented by the same logic. Hence, the axis of the problem of the further improvement of the model of governance in the Republic of Armenia should be transformed from the issue of making a choice between this or that form of governance, and the main attention should be focused on improving the mechanisms of separation and balance of powers, as well as forming and strengthening constitutional and political traditions and culture.
Keywords: parliamentary; presidential; semi-presidential forms of governance; constitutional reforms; constitutional and political culture; politics; legal convergence